Advanced Windows PowerShell scripting : from cmdlets and custom views to object creation and automation - Yoder, Jason (O'Reilly, 2016)
"In this Advanced Windows PowerShell Scripting training course, expert author Jason Yoder will take you beyond the basics of Windows PowerShell, teaching you how to create cmdlets, create custom views, and much more. This course is designed for users that are already familiar with PowerShell. You will start by learning how to create a script and module. From there, Jason will teach you about advanced objects, the PowerShell pipeline, and PowerShell demoting, including how to enable remoting, one-to-one remoting, and one-to-many remoting. This video tutorial also covers finding sources of information and using external information. Finally, you will learn about automating administration, including background jobs, scheduled jobs, and reporting. Once you have completed this computer based training course, you will have gained an advanced working knowledge of Windows PowerShell. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.